2022
DOI: 10.1186/s43066-022-00171-6
|View full text |Cite
|
Sign up to set email alerts
|

Liver injury with COVID-19: laboratory and histopathological outcome—systematic review and meta-analysis

Abstract: Background The novel coronavirus severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection has been predominantly linked to respiratory distress syndrome, but hepatic injury has also been reported. The mechanism of liver injury is poorly understood. This review aimed to systematically review the current data through laboratory tests and liver tissue pathology to ascertain the correlation of liver involvement in SARS-CoV-2 infection patients. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 40 publications
0
15
0
Order By: Relevance
“…This systematic review has several strengths. Unlike previous meta-analyses on related topics [ 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 ], this study: (i) involves a comprehensive analysis of a large number of studies that are based in different countries in the world; (ii) includes many articles that were published in 2021, after the introduction of the Delta strain; (iii) analyzes only peer-reviewed data; (iv) assesses the extensive analysis of the source of the heterogeneity and bias in the studies; and (v) compares the risk of admission to the ICU vs. no admission among hospitalized COVID-19 patients, and is stratified on the basis of comorbidities and demographic status.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…This systematic review has several strengths. Unlike previous meta-analyses on related topics [ 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 ], this study: (i) involves a comprehensive analysis of a large number of studies that are based in different countries in the world; (ii) includes many articles that were published in 2021, after the introduction of the Delta strain; (iii) analyzes only peer-reviewed data; (iv) assesses the extensive analysis of the source of the heterogeneity and bias in the studies; and (v) compares the risk of admission to the ICU vs. no admission among hospitalized COVID-19 patients, and is stratified on the basis of comorbidities and demographic status.…”
Section: Discussionmentioning
confidence: 92%
“…However, the associations with other comorbidities have been less clear, such as with cancer, chronic liver disease, diabetes, and kidney disease. While several meta-analyses studies report an increased risk of death in COVID-19 patients with diabetes [ 5 , 11 , 19 ], cancer [ 20 , 21 , 22 ], liver disease [ 23 , 24 , 25 ], and kidney disease [ 26 , 27 , 28 , 29 ], some report the lack of correlation between these comorbidities and the disease progression or the clinical outcomes of COVID-19 patients [ 30 , 31 , 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…They concluded that COVID-19 infection was not associated with a specific histopathological pattern of the liver [ 62 ]. In any case, one recently published meta-analysis demonstrated that the severity of COVID-19 was associated with aberrant liver function tests [ 63 ]. Interesting findings regarding the temporal evolution of COVID-19-associated cardiopathy were reported by Haslbauer et al [ 64 ].…”
Section: Aspects Of Host Response—how Specific Are They For Covid-19?mentioning
confidence: 99%
“…However, patients infected with SARS-CoV-2 often suffer other devastating end-organ injuries[ 10 ], suggesting the virus causes systemic infection and inflammation. These observations have prompted interest in the extra-pulmonary manifestations of COVID-19[ 11 ], including those in the heart[ 12 , 13 ], intestines[ 14 , 15 ], kidney[ 16 ], reproductive system[ 17 , 18 ], and the liver, where the effect of SARS-CoV-2 is poorly understood[ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…COVID-19 associated liver injury (COVALI) is a clinical entity encompassing any abnormal liver function test present in individuals positive for SARS-CoV-2[ 20 ]. Currently there are no specific or unique diagnostic criteria for COVALI relative to other causes of transaminitis[ 21 ] which complicates the process of synthesizing evidence from clinical studies.…”
Section: Introductionmentioning
confidence: 99%